Diagnóstico situacional de la labor docente y de la oferta de formación de educadores rurales en Costa Rica - Vargas Fallas, Claudio Antonio (2008)
The article explores the performance of rural teachers in Costa Rica and analyses the curricula taught in public universities. It also examines limitations and advantages of teaching in rural areas and the way teachers face the challenges imposed by this kind of context in terms of cultural, economical and social particularities. Finally, based on the information collected in this investigation, a series of contents are presented in order to enrich the curricula of teacher training universities and to offer to their students, future teachers, the necessary tools to work in the rural area.